Energy, Carbon and Cost Benefits of Bus Network Optimisation in the City of Batumi, Republic of Georgia - Michael Saunders (European Regional Science Association (ERSA), 2011)
The City of Batumi, Georgia had suffered from a complete disintegration in public transport after the collapse of the Soviet Union in the 1990s. However, recently the city has undergone a revival period that has seen investment in all municipal sectors, including public transport. The municipally owned bus company's bus fleet has been increased from 20 buses to 101 buses and has the potential to serve the entire 150,000 population of the coastal city. However, the initial route planning was not based upon the ability for passengers to transfer from one route to another; this created many inefficient parallel route sections. This inefficiency is affecting the company financially and causing additional energy use and carbon emissions. A study was commissioned by the City and Bus Company with the aid of the European Bank of Reconstruction and Development to optimise the bus routes and create a bus network that includes the ability to transfer from one route to another. The initial results have shown that at least 30% operational, energy and carbon savings can be achieved following a two year action plan that includes creation of a central transfer terminal and optimisation of bus routes. The new bus routes cover the same territory at even lesser intervals which also benefits the passenger. In addition, the citizen of Batumi will have complete access to the whole city via public transport, making the city more accessible for those reliant on public transport or who chose it over the motor vehicle.
Keywords: 330